Polyneuropathy: a poetic diagnosis. (10th July 2012) - Pattani, Reena; Rozenberg, Dmitry; Mozessohn, Lee; Hicks, Lisa
Abstract : A 60-year-old woman presented with subacute progressive lower extremity weakness. This was associated with a 40lb weight loss and fevers. She was previously healthy, aside from renal transplantation 9 years earlier for end stage renal disease resulting from IgA nephropathy. On examination, she had clubbing, a single lymph node in the right cervical chain, and objective findings of lower extremity weakness with lower motor neuron findings. Investigations revealed a thrombocytosis and elevated CSF protein. Electromyographic evidence of diffuse polyradiculopathy with demyelination was documented. On imaging, she had a large lytic/sclerotic lesion in the right scapula measuring 8 cm, a pericardial effusion, and borderline splenomegaly. Pathological assessment of the excised lymph node revealed Castleman-like changes; biopsy of the right scapular lesion revealed λ-restricted plasma cells, in the absence of a monoclonal protein in the bone marrow or periphery. A diagnosis of POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes) with plasmacytoma was established; a post-transplant lymphoproliferative disorder was suspected.